CITRA MASKULINITAS NEGATIF DALAM NOVEL DI TANAH LADA KARYA ZIGGY ZEZSYAZEOVIENNAZABRIZKIE - Hairira, Offerina Diva; Karimah, Nurul; Amanda, Saskia; Hadiansyah, Firman (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2023)
Masculinity can not only be found in novels, but is often encountered in everyday life. Examining this novel through a masculinity approach can reveal the form of masculinity depicted in the novel Di Tanah Lada. The aim of this research is to describe negative forms of masculinity in the novel Di Tanah Lada by Ziggy Zezsyazeoviennazabriskie which is analyzed based on Bourdie's theory regarding depictions of masculinity such as the social construction of the body, the incorporation of domination, symbolic violence, women in the symbolic wealth economy, virility and violence. It is hoped that the benefits of this research can be a source of reading reference as well as a contribution to the field of literary studies, especially masculinity.The method used by the author in this research is a qualitative descriptive research method. The data collection technique in this research was carried out by reading and taking notes using data analysis techniques which went through three stages, namely data reduction, data presentation and drawing conclusions. The results of the research show that there are 10 data in the novel Di Tanah Lada by Ziggy Zezsyazeoviennazabriskie which reflect the negative masculinity image of the character Papa who has a temperamental nature, uses power for bad things, does not respect women, often commits violence and insults, is not a good husband in a family and There is data that shows inequality in men because of existing masculinity, namely the idea that a man cannot cry.